The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2176/nmc.51.707
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Longitudinal Clival Fracture in a Child -Case Report-

Abstract: A 7-year-old boy presented with a longitudinal clival fracture following a traffic accident. The boy presented only with temporary unconsciousness despite suffering a fracture of the clivus. Fractures of the clivus are often caused by severe head trauma, and the mortality rate is high due to coexisting injury of the adjacent vessels, brain stem, and lower cranial nerves. Review of the radiological and clinical findings of longitudinal clival fractures found that all reported pediatric patients with longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The majority of longitudinal fractures in adults were associated with frontal impact in contrast to the 5 published pediatric cases that were all associated with occipital impact (see Table 1). 4 Our patient is the first pediatric case with a longitudinal fracture associated with frontal impact in the published literature. To the best of our knowledge, no other cases of transient DI in children secondary to longitudinal clivus fractures have been reported.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The majority of longitudinal fractures in adults were associated with frontal impact in contrast to the 5 published pediatric cases that were all associated with occipital impact (see Table 1). 4 Our patient is the first pediatric case with a longitudinal fracture associated with frontal impact in the published literature. To the best of our knowledge, no other cases of transient DI in children secondary to longitudinal clivus fractures have been reported.…”
Section: Discussionmentioning
confidence: 79%
“…Longitudinal clivus fractures are rare in children, with only five cases published in the English literature to date. [1][2][3][4] In a large series, Ochalski et al reported an incidence of 0.21% among patients with suspected closed head injury and 2.4% of all cranial fractures admitted to their hospital. 5 The clivus is a deep-seated, wellprotected structure, thus fractures are usually only seen in high-velocity impact situations such as that our patient had.…”
Section: Discussionmentioning
confidence: 99%
“…10 Clival fractures also have high mortality rates (12.4%-80%) and can be associated with occipital/foramen magnum/condyle fractures (68.8%) and sella/carotid canal fractures (81.3%). [10][11][12] Weaknesses of this study include a relatively small sample size and repeated sequential impacts being made on cadaver heads with preexisting bony fractures from previous impacts. With each impact, postimpact fracture patterns will be affected by preexisting bony fractures because focal stress points will change with developing bony fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, clival fractures are also rarely seen, observed in 0.21% to 0.56% of all head injuries . Clival fractures also have high mortality rates (12.4%–80%) and can be associated with occipital/foramen magnum/condyle fractures (68.8%) and sella/carotid canal fractures (81.3%) …”
Section: Discussionmentioning
confidence: 99%
“…In the previously mentioned case, the atypical fracture shape cannot be explained by osteoporosis, because the patient was young. In many reported cases, the main mechanism was occipital trauma ( 6 ), which fractured the low-resistance floor of the anterior skull base, due to the combined effect of osseous and cerebral oscillations-causing a pressure gradient inside the skull. Atypical bone injury is considered to be related to the state of the clival bone, including the development of a well-pneumatized sphenoid sinus.…”
mentioning
confidence: 99%